"The Effect Of The Polya Strategy On The Achievement Of Social Studies Among First-Year Intermediate School Students" (Journal of the College of Basic Education, 2024)
The purpose of the present study is to determine how the Polya approach affects first-year middle school students' social studies performance. The Umm Al-Muminin Girls' Middle School first-year students in the city of Baghdad for the academic year 2023–2024 were the only subjects of the present study. An experimental group and a control group with pre- and post-tests were part of the researcher's partial control experimental design. There were sixty-eight female students in the first intermediate grade that made up the research sample: thirty-four were in the experimental group and thirty-four were in the control group. By creating an accomplishment exam with forty multiple-choice questions, the researcher was able to assess the factors thatwere reliant on the study. Its reliability and validity have been established. The T-test, arithmetic averages, and suitable statistical treatments were applied to the data in order to examine it. Additionally, the Cronbach's alpha equation and the achievement test results demonstrated statistically significant differences favoring the experimental group that used the Polya technique for their studies. For the duration of the current semester, the research experiment was conducted.